Information security education. Education in proactive information security : 12th IFIP WG 11.8 World Conference, WISE 12, Lisbon, Portugal, June 25–27, 2019, Proceedings /: 12th IFIP WG 11.8 World Conference, WISE 12, Lisbon, Portugal, June 25–27, 2019, Proceedings. (2019) - Unknown
No abstract available